Los bibliotecarios enlace: avanzar hacia el éxito - Rovira, Anna (Anuario ThinkEPI, 2015)
Reseña del informe: Kenney, Anne R.;Â Kroch, Carl A. (2014). Leveraging the liaison model: From defining 21st century research libraries to implementing 21st century research universities. Ithaka S+R. http://www.sr.ithaka.org/blog-individual/leveraging-liaison-model-defining-21st-centuryresearch-libraries-implementing-21st